Species identification of dermatophytes in paraffin‐embedded biopsies with a new polymerase chain reaction assay targeting the internal transcribed spacer 2 region and comparison with histopathological features. (1st April 2016) - Eckert, J.C.; Ertas, B.; Falk, T.M.; Metze, D.; Böer‐Auer, A.
Summary: Background: Dermatophytosis is a very common skin infection with a broad clinical spectrum. Biopsies are often used to confirm the diagnosis, especially when the clinical presentation is unusual. Not uncommonly, organisms are hard to find even with periodic acid–Schiff stains. Polymerase chain reaction (PCR) for dermatophytes can be used in such cases. Objectives: To test a new PCR assay allowing species identification of dermatophytes on paraffin‐embedded biopsies, and to reassess histopathological criteria for diagnosis of dermatophytosis. Methods: In total, 121 biopsies of 92 patients with clinical suspicion of tinea were included. In 42 samples the clinical diagnosis had been confirmed histopathologically, and in 79 no fungal elements had been identified. PCRs targeting the internal transcribed spacer (ITS)2 region of dermatophytes were performed on the biopsies with subsequent sequencing. Sections were reassessed for the presence/absence of hyphae/spores, pattern and composition of infiltrate, and epidermal/follicular changes. Patient charts were reviewed for clinical data. Results: The new ITS2 PCR assay detected 94% of the dermatophyte infections (compared with 79% identified by microscopy). Trichophyton rubrum was the dominant species (89%), and other species identified were Trichophyton verrucosum (2%), Microsporum canis (4%), Epidermophyton floccosum (2%) and Trichophyton interdigitale (4%). In particular, infections with T. interdigitale and manifestations with prominent spongiosis were not diagnosed histologically. Intracorneal neutrophils, which have been emphasized as a histopathological clue to dermatophytosis, were present in only 46% of PCR‐positive samples. Conclusions: Molecular species identification of dermatophytes via ITS2 PCR can easily be implemented in a routine dermatopathology setting. It is fast and highly specific and improves the sensitivity of histopathological diagnosis of dermatophytosis.